ANALISIS MANAJEMEN RESIKO PEMBIAYAAN PEER TO PEER LENDING (P2PL) FINTECH SYARIAH (STUDI KASUS PADA PT ALAMI SYARIAH) - Dewi Fatmala Putri; Zuraidah Zuraidah (Journal of Management and Social Sciences, 2022)
One form of progress in the current financial sector is evidenced by the adaptation of Fintech, which stands for sharia P2PL Financial Technology. Financial institutions in carrying out their activities cannot be avoided what is called risk. That's why to gain profit and customer trust, financial institutions are required to have good risk management, especially fintech companies that offer convenience and efficiency in transactions, so they will be very vulnerable to various types of risks in the financing process that can affect the sustainability of the fintech itself. fintech companies, before channeling financing to potential recipients of funds, also need to be able to pay attention to various risks that may arise, both predictable and not, and also have techniques for mitigating risks from all possibilities that may occur in the future, so there is a need for strategic steps and ways to minimize existing risks. This type of research is empirical and uses a qualitative approach with secondary data source. From the explanation, it can be said that PT ALAMI Sharia has carried out Sharia fintech P2PL transactions that are following existing economic principles starting from the identification of potential recipients of funds, analysis carried out by PT ALAMI and risk mitigation carried out by PT ALAMI Syariah.